Study on the influence of glass encapsulating on the hygroscopicity of high temperature phase change heat storage materials. Issue 5 (April 2020) - Zhang, Gaoqun; Deng, Zhanfeng; Lu, Yunkun; Hao, Junjie; Ren, Zhongkai; Chang, Liang; Tan, Hui; Cai, Linhai; Xu, Guizhi; Wang, Tianhao
Abstract: In this paper, Na2 CO3 -K2 CO3 / MgO phase change composite was coated on the surface of glass by spray plating, which solved the problem of absorbing moisture and pulverizing of molten salt / MgO phase change thermal storage material in high humidity environment, and reduced the absorbing moisture and pulverizing rate from 31% to 19% without affecting the latent heat of phase change thermal storage material.